(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Prawira AY, Novelina S, Farida WR, Darusman HS, Agungpriyono S. 2019. Lectin histochemical study of the quill sebaceous gland in the dorsal skin of the Sunda porcupine (Hystrix javanica). Biodiversitas 20: 2677-2684. In the Sunda Porcupine skin, the sebaceous glands of the quill follicles are multi-lobed alveolar and better developed than those of hair follicles. Using lectin histochemistry, we have studied the distribution of sugar-binding in the sebaceous glands of quills in comparison with those of hairs in six adult Sunda Porcupines. The skin samples from the thoracodorsal and lumbosacral regions were collected by biopsy procedure and processed for histology, histochemistry, and lectin histochemistry. The results showed that the lectin binding patterns are similar in secretory acinar parts of both types of sebaceous glands. The acini and excretory duct contained neutral carbohydrate and sugar residues. The acini also contained alpha D-mannose sugar residue, while the non-secretory excretory duct and debris in the lumen contained alpha-D-mannose, alpha-L-fucose, and ?>?-N-acetylgalactosamine, and complex type N-glycan (oligosaccharide) sugar residues, as well. The present findings allowed us to suggest, that in Sunda Porcupine functions of the sebaceous glands of quills are more complex and active compared to those of the hairs.